PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF CLITORIA TERNATEA LEAVES AGAINST STAPHYLOCOCCUS AUREUS - SONALI NIGAM; P.N.SHRIVASTAVA (International Journal of Pharma and Bio Sciences, 2013)
Plants have played a major role in the production of biological compounds for the formation of drugs. Their role may either become a base for the development of medicine, a natural blue print for the development of new drugs or a phytomedicine to be used for the treatment of diseases. Secondary metabolites are responsible for medicinal activity of plants. Clitoria ternatea commonly known as butterfly pea has diuretic and laxative effect. It also possess anti-inflammatory and anti-pyretic properties. Hence in the present study phytochemical and antimicrobial activity was carried out to confirm the presence of various phytochemical like saponins, terpenoids, steroids, tannins and to determine the minimum inhibitory concentration of extracts. The results suggest that the phytochemical properties for curing various ailments and possess potential antioxidant and leads to the isolation of new and novel compounds. The methanolic extract inhibited the growth of Gram positive bacteria Staphylococcus aureus.In reference to the role of plants in ethnomedicines and in traditional system the presence of phyotchemical consitutents in them have been studied.